2017
DOI: 10.18203/issn.2454-5929.ijohns20174321
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between fat myringoplasty and temporalis fascia tympanoplasty in moderate to large central perforation of pars tensa of tympanic membrane

Abstract: <p class="abstract"><strong>Background:</strong> To compare the efficacy between fat graft (FG) and temporalis fascia (TF) graft in tympanic membrane perforations larger than 4mm size or involvement of &gt;25% of tympanic membrane.</p><p class="abstract"><strong>Methods:</strong> This prospective study was carried out during December 2015 to January 2016, for a period of 13months at our Otolaryngology Department. All study patients, who fit into inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In a series of 30 patients who received a FG, Ambani et al 14 reported a success rate of 53.3%. In their series, the ABG decreased to <10 dB in 12 (40%) patients, was unchanged after the operation in 10 (33.3%) patients, and increased after the operation in 8 (26.6%) patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a series of 30 patients who received a FG, Ambani et al 14 reported a success rate of 53.3%. In their series, the ABG decreased to <10 dB in 12 (40%) patients, was unchanged after the operation in 10 (33.3%) patients, and increased after the operation in 8 (26.6%) patients.…”
Section: Discussionmentioning
confidence: 98%
“…13 Although the regenerative effects of fat grafting into the recipient bed are known, most otolaryngologists do not use FGs often and prefer other materials, such as TF or perichondrium, to close tympanic perforations. 14 It has been demonstrated convincingly that FGs contain viable adipose stem cells (ASCs). It has also become apparent that white adipose tissue is the most suitable autologous injectable filler for correcting soft tissue defects.…”
Section: Discussionmentioning
confidence: 99%